(untitled) (Actual Problems of Psychology in Educational Institutions, 2020)
Abstract. The article is devoted to the analysis of the problem of detecting conflict behavior in adolescence. The author outlines the content of conflict and conflict situation, discusses the main causes of conflict, makes a comparative analysis of constructive and destructive conflicts, states both positive and negative functions of conflicts, describes different styles of behavior in conflict situation. There is clarified that characteristic of adolescence is an increase in the proportion to problematic behaviors in conflict. The article presents the results of an empirical study pointing to changes in styles of conflict behavior during the process of becoming an individual, in particular the tendency to increase the use of oppositional patterns of behavior, activity in the fight against constant customs and laws, increasing envy and hatred to others